FEATURES OF PRE-ROMAN HISTORY OF SPAIN AND MODERN TIME: WHERE ARE SOURCES OF SEPARATISM? - A. A. Orlov (Vestnik MGIMO-Universiteta, 2013)
Presently in collective consciousness there was a steady perception of Spain as the safe state entering into group of the countries, being a support of the European integration. The impression was made that Spain, despite difficulties of its historical development, at last found the national identity, having created from regions and national lands making it the new multicultural community fastened in a whole by a tolerant, educated and authoritative monarchy. However the world economic crisis which has begun in 2008 destroyed the Spanish idyll, having aggravated old and having generated new contradictions. Traditionally painful problem for Spain was existence of centrifugal tendencies at the heart of which two main reasons lay: manifestations of the nationalism peculiar to those areas where Catalan, Basque and Galician nationalities historically lived, and a regionalism caused by aspiration of local elite to bigger distance from Madrid. Considering features of pre-Roman history of Spain, the author seeks to understand, whether sources of modern separatism can originate in an extreme antiquity. Following the results of research the conclusion is drawn that most boldly "link of times" is traced on the example of Basques, the part of which intellectual elite seeks to use features of origin and historical development of these people for a reinforcement of current nationalist and separatist trends. The author considers that the history has to serve as the bridge between the people, instead of put up between them a new wall.